On the Nature of Null Clausal Complements in Japanese. (9th April 2014) - Kasai, Hironobu
Abstract This paper argues that the null clausal complement in Japanese is not derived via CP ellipsis but is rather an instance of pro. The availability of sloppy interpretation in the construction under investigation apparently argues that ellipsis is involved there, but it is revealed under close scrutiny of the sloppy interpretation in question that the null clausal complement behaves like deep anaphora, not like surface anaphora.